How do you solve x^2-2x-1=x+3?

3 Answers
Apr 13, 2018

x=4
x=-1

Explanation:

First, get 0 on one side.
(x^2-2x-1) -(x+3)=x+3 -(x+3)

x^2-3x-4=0

Next, factor this equation.
(x-4)(x+1)=0
Therefore,
(x-4)=0
x=4
or
(x+1)=0,
x=-1

You can verify this using FOIL:
=x^2+x-4x-4
=(x^2-3x-4)

Apr 13, 2018

x=-1
x=4

Explanation:

x^2-2x-1=x+3

x^2-2x-1-x-3=0

x^2-3x-4=0

x^2-4x+x-4=0

x(x-4)+1(x-4)=0

(x+1)(x-4)=0

x+1=0
x=-1

x-4=0
x=4

Apr 13, 2018

x=-1,x=4

Explanation:

Consider the given equation
x^2-2x-1=x+3

Subtract x+3 from both sides (Or bring all terms to the left-hand side)

x^2-2x-1-x-3=x+3-x-3

Thus,
x^2-2x-1-x-3=0

Add like terms
x^2-3x-4=0

Split middle term so as to obtain (-4) as product and (-3) as sum
x^2+x-4x-4=0

Take common factors out from paired terms
x(x+1)-4(x+1)=0

Then,
(x+1)(x-4)=0
x+1=0 or x-4=0
x=-1 or x=4